Enhanced ciprofloxacin removal by sludge-derived biochar: Effect of humic acid. (September 2019) - Luo, Kun; Pang, Ya; Yang, Qi; Wang, Dongbo; Li, Xue; Wang, Liping; Lei, Min; Liu, Jiamei
Abstract: Humic acid (HA) is ubiquitous in the environment, and its effect on the adsorption of pollutants onto biochar (BC) has been widely investigated. However, the catalytic degradation of organic contaminants induced by persistent free radicals (PFRs) in BC is not negligible. In this study, two different source of external HA, dissolved HA and coated HA, was employed to assess the effect of HA on the degradation of organic contaminant ciprofloxacin (CIP) by PFRs in BC. Results showed that relatively low concentration of dissolved HA promoted the removal of CIP from 59.78% (control) to 66.70% (5 mg/L dissolved HA) by BC, but higher concentration of dissolved HA inhibited. By contrast, coated HA altered the characteristics of BC and had negative impact on organics removal. The removal of CIP by BC in the presence of HA did not have a great difference at pH 6–9, and increasing dissolved oxygen promoted CIP degradation. In addition, the contribution of CIP removal led by adsorption was 47.61%, 41.62% and 47.84% respectively for BC, BC + dissolved HA and 1% HA coated BC. Correspondingly, the contribution of CIP removal led by OH induced from PFRs in BC was respectively 21.88%, 35.58% and 25.11%, and the contribution led by PFRs themselves oxidation was 30.51%, 22.80% and 27.05%, respectively. The calculated contributions of adsorption and degradation to CIP removal demonstrated that the contribution of degradation to CIP removal led by OH increased, while the contribution led by PFRs themselves oxidation was inhibited in the presence of dissolved and coated HA. Highlights: Low concentration of dissolved HA promotes, but high inhibits CIP removal. Coated HA alters the properties of BCs and has negative impact on CIP removal. The contribution of degradation led by .OH increased in the presence of HA. The contribution of degradation led by PFRs was inhibited in the presence of HA.